2022
DOI: 10.1097/rct.0000000000001425
|View full text |Cite
|
Sign up to set email alerts
|

Does the Thymus Index Predict COVID-19 Severity?

Abstract: Background The COVID-19 (coronavirus disease 2019) pandemic is a global health emergency that is straining health care resources. Identifying patients likely to experience severe illness would allow more targeted use of resources. This study aimed to investigate the association between the thymus index (TI) on thorax computed tomography (CT) and prognosis in patients with COVID-19. Methods A multicenter, cross-sectional, retrospective study was conducted between March 17 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…We recently found that among severely ill COVID-19 patients with pulmonary involvement, thymic reactivation, evidenced by enhanced thymic production of new lymphocytes, with or without thymus enlargement, was associated with a more favorable outcome (6), an observation that was confirmed by subsequent studies (7,8). The origin of the enhanced thymic function observed in this subgroup of patients with COVID-19 remained unexplored.…”
Section: Introductionmentioning
confidence: 80%
“…We recently found that among severely ill COVID-19 patients with pulmonary involvement, thymic reactivation, evidenced by enhanced thymic production of new lymphocytes, with or without thymus enlargement, was associated with a more favorable outcome (6), an observation that was confirmed by subsequent studies (7,8). The origin of the enhanced thymic function observed in this subgroup of patients with COVID-19 remained unexplored.…”
Section: Introductionmentioning
confidence: 80%